Pain and health-related quality of life in patients with hypophosphatasemia with and without ALPL gene mutations - Santurtún, Maite; Mediavilla-Martinez, Eva; Vega, Ana I.; Gallego, Natalia; Heath, Karen E.; Tenorio, Jair A.; Lapunzina, Pablo; Riancho-Zarrabeitia, Leyre; Riancho, José A. (Frontiers in Endocrinology, 2022)
Background Low serum alkaline phosphatase levels are the hallmark of hypophosphatasia, a disorder due to pathogenic variants of the ALPL gene. However, some patients do not carry ALPL variants and the cause of low alkaline phosphatase remains unknown. We aimed to determine health-related quality of life in adults with low alkaline phosphatase and explore the differences between patients with and without ALPL mutations. Methods We studied 35 adult patients with persistently low alkaline phosphatase unrelated to secondary acquired causes who had ALPL sequenced, and 35 controls of similar age. Three questionnaires about body pain (Brief Pain Inventory, BPI), physical disability (Health Assessment Questionnaire Disability Index, HAQ-DI), and health-related quality of life (36-item Short-Form Health Survey, SF-36) were delivered by telephone interviews. Results The mean BPI intensity and interference scores were higher in the patient group (p=0.04 and 0.004, respectively). All domains of the HAQ instrument tended to score better in the control group, with significant differences in the “reach” score (p=0.037) and the overall mean score (0.23 vs 0.09; p=0.029). Patients scored worse than controls in several SF-36 dimensions (Role physical, p=0.039; Bodily pain p=0.046; Role emotional, p=0.025). Patients with and without pathogenic variants scored similarly across all tests, without between-group significant differences. Conclusions Patients with persistently low levels of alkaline phosphatase have significantly worse scores in body pain and other health-related quality of life dimensions, without differences between patients with and without pathogenic variants identified in ALPL gene. This is consistent with the latter ones carrying mutations in regulatory regions.